PERANAN HUKUM DALAM GLOBALISASI EKONOMI - Ngadino Ngadino (UNISSULA, 2014)
The role of law in the development of economic globalization among the nation’s increasingly important role, particularly regulate all forms of advances in information technology, communications, transportation in international transaction. economic globalization regulate human activities in meeting human needs through trade in goods and services, be right revealer of new powerswhich requires the establishment of public welfare, running a variety of interests between citizens who are heading on technology-based society, in addition to the law here to protect, organize and plan economic life so that the dynamics of economic activity that can be directed to the progress and welfare of the entire community, economic globalization cannot be avoided by any country. With compliance with international legal norms, the harmony and well-being of society can be achieved.